Femoroacetabular Impingement: Prevalent and Often Asymptomatic in Older Men: The Osteoporotic Fractures in Men Study. Issue 8 (August 2015) - Nardo, Lorenzo; Parimi, Neeta; Liu, Felix; Lee, Sonia; Jungmann, Pia M.; Nevitt, Michael C.; Link, Thomas M.; Lane, Nancy E.
Abstract: Background: The epidemiology of femoroacetabular impingement (FAI) is important but incompletely understood, because most reports arise from symptomatic populations. Investigating the prevalence of FAI in a community‐based cohort could help us better understand its epidemiology and in particular the degree to which it might or might not be associated with hip pain. Questions/purposes: The purposes of this study were (1) to evaluate the proportion of older (≥ 65 years of age) men with morphologic abnormalities consistent with FAI; and (2) to assess the association of the morphologic abnormalities with prevalent radiographic hip osteoarthritis (OA) and hip pain. Methods: Anteroposterior radiographs were obtained in 4140 subjects (mean age ± SD, 77 ± 5 years) from the Osteoporotic Fractures in Men study. We assessed each hip for cam, pincer, and mixed FAI types using validated radiographic definitions. Both intra‐ and interobserver reproducibility were > 0.9. Radiographic hip OA was assessed by an expert reader (intraobserver reproducibility, 0.7‐0.8) using validated methods, and summary grades of 2 or greater (on a scale from 0 to 4) were used to define radiographic hip OA. Covariates including hip pain in the last 30 days were collected by questionnaires that were answered by all patients included in this report. Logistic regressions with generalized estimating equations were performed to evaluate the association of radiographic features of FAI and arthrosis. Results: Pincer, cam, or mixed types of radiographic FAI had a prevalence of 57% (1748 of 3053), 29% (886 of 3053), and 14% (419 of 3053), respectively, in this group of older men. Both pincer and mixed types of FAI were associated with arthrosis but not with hip pain (odds ratio [OR], 1.63; 95% confidence interval [CI], 1.25‐2.13; p < 0.001 for pincer and OR, 2.49; 95% CI, 1.65‐3.76; p < 0.001 for mixed type). Patients with hips characterized by cam‐type FAI had slightly reduced hip pain without the presence of arthrosis compared with hips without FAI (OR, 0.82; 95% CI, 0.68‐0.99; p = 0.037). A center‐edge angle > 39° and a caput‐collum‐diaphyseal angle < 125° were associated with arthrosis (OR, 1.53; 95% CI, 1.22‐1.94; p < 0.001 and OR, 2.09; 95% CI, 1.24‐3.51; p = 0.006, respectively), but not with hip pain (OR, 0.89; 95% CI, 0.77‐1.03; p < 0.108 and OR, 0.99; 95% CI, 0.67‐1.45; p = 0.945, respectively). An impingement angle < 70° was associated with less hip pain compared with hips with an impingement angle ≥ 70° (OR, 0.76; 95% CI, 0.61‐0.95; p = 0.015). Conclusions: FAI is common in older men and represents more of an anatomic variant rather than a symptomatic disease. This finding should raise questions on how age, activities, and this anatomic variant each contribute to result in symptomatic disease. Level of Evidence: Level III, prognostic study.